Design of an automated solar concentrator for the pyrolysis of scrap rubber. (1st September 2015) - Zeaiter, Joseph; Ahmad, Mohammad N.; Rooney, David; Samneh, Bechara; Shammas, Elie
Highlights: Design of a solar concentrator with high focal-point temperatures. Development of an automated continuous solar tracking system. Catalytic pyrolysis to convert waste rubber tire to gas and liquid products. The liquid components had high yields of C10 –C29 hydrocarbons. The gaseous components were mainly propene and cyclobutene. Abstract: An automated solar reactor system was designed and built to carry out catalytic pyrolysis of scrap rubber tires at 550 °C. To maximize solar energy concentration, a two degrees-of-freedom automated sun tracking system was developed and implemented. Both the azimuth and zenith angles were controlled via feedback from six photo-resistors positioned on a Fresnel lens. The pyrolysis of rubber tires was tested with the presence of two types of acidic catalysts, H-beta and H-USY. Additionally, a photoactive TiO2 catalyst was used and the products were compared in terms of gas yields and composition. The catalysts were characterized by BET analysis and the pyrolysis gases and liquids were analyzed using GC–MS. The oil and gas yields were relatively high with the highest gas yield reaching 32.8% with H-beta catalyst while TiO2 gave the same results as thermal pyrolysis without any catalyst. In the presence of zeolites, the dominant gasoline-like components in the gas were propene and cyclobutene. The TiO2 and non-catalytic experiments produced a gas containing gasoline-like products of mainly isoprene (76.4% and 88.4% respectively). As for the liquids they were composed of numerous components spread over a wide distribution of C10 to C29 hydrocarbons of naphthalene and cyclohexane/ene derivatives.